Using inertial sensors for assessing movement symmetries in trotting dogs : a feasibility study - Stenman, Anders (SLU/Dept. of Clinical Sciences (until 231231), 2019)
Lameness or other disturbances in the musculoskeletal system are common reasons why dog owners seek veterinary care. The lameness is most often associated with pain, degenerative changes in joints or muscles, or injury.